Postural stability and regulation before and after anterior cruciate ligament reconstruction – A two years longitudinal study. (July 2019) - Bartels, Thomas; Brehme, Kay; Pyschik, Martin; Pollak, Ruben; Schaffrath, Nicola; Schulze, Stephan; Delank, Karl-Stefan; Laudner, Kevin; Schwesig, René
Abstract: Objectives: To evaluate postural regulation and stability among patients who underwent anterior cruciate ligament reconstruction (ACLR) and rehabilitation over a two-year follow-up period. Design: Longitudinal; Setting: Biomechanics laboratory; Participants: 30 ACLR patients (32.0 ± 12.2 years, 14 males) with isolated ACL rupture. Main outcome measures: Postural regulation was tested before ACLR, as well as at six-weeks, twelve-weeks, six-months, one-year and two-years post-ACLR and standardized rehabilitation. Postural regulation was measured for stability indicator (ST), weight distribution index (WDI), synchronization (foot coordination) and sway intensities (postural subsystems). Results: Significant time effects (pre-vs. two-years postoperative) were found for WDI (ηp 2 = 0.466), synchronization (ηp 2 = 0.368), mediolateral weight distribution (ηp 2 = 0.349), ST (ηp 2 = 0.205), visual/nigrostriatal systems (ηp 2 = 0.179) and peripheral-vestibular system (ηp 2 = 0.102). The largest difference (preoperative: ηp 2 = 0.180) to the matched sample was calculated for WDI. The most significant differences to the matched sample were observed for ST (preoperative: ηp 2 = 0.126; six-weeks postoperative: ηp 2 = 0.103) and WDI (preoperative: ηp 2 = 0.180; six-weeks postoperative: ηp 2 = 0.174). Conclusion: ACLR and rehabilitation influence postural subsystems, postural stability, weight distribution and foot synchronization. Normalization of mediolateral weight distribution requires one year following ACLR. The ACLR leads to a suppression of the somatosensory and cerebellar system which was compensated by a higher activity of the visual and nigrostriatal systems. Highlights: ACLR patients showed significant improvements (pre-erative vs. two-year postoperative) in several areas of postural regulation. Load distribution to the heel significantly improved between six months and two years post-surgery (left-sided injury). An increased forefoot load was also observed at the end of the observation period. Lateral load distribution for patients with left-sided injury had the most (4) significant changes during the observation periods.